A study of examination timetable problem in UMP - Mohd Nizam, Mohmad Kahar; Ku Saimah, Ibrahim; Suryanti, Awang; Zalili, Musa; Rohani, Abu Bakar; Tuty Asmawaty, Abdul Kadir
The examination timetabling problem involves the task of assigning the examinations into a limited number of timeslots and rooms with the aim of satisfying all the hard constraints. Most of the reported research in the literature starts with constructing the initial timetable by scheduling all the examinations and then performs an improvement on the timetable. In this research, we investigate a real world examination timetabling problem from Universiti Malaysia Pahang (UMP). UMP examination timetabling dataset is a capacitated dataset which contains additional constraints, in addition to those commonly used in the literature. The proposed algorithms start with constructing the initial timetable using the graph heuristic methods. The entire process runs until all of the examinations are assigned successfully. An improvement on the solution was implemented using step-count hill climbing and late acceptance hill climbing. The proposed approaches are tested on two benchmark datasets, namely Toronto dataset and the Universiti Malaysia Pahang (UMP) dataset. The experimental results show that the proposed approaches are able to produce good quality solution when compared to the solutions from the proprietary software used by UMP. Additionally, our solutions satisfy to all the hard constraints which the current systems fails to do.